Algebra
-
If x + 3 = 1 then the value of x3 is 3 x
-
View Hint View Answer Discuss in Forum
x + 3 = 1 3 x ⇒ x2 + 9 = 1 3x
⇒ x2 + 9 = 3x
⇒ x2 – 3x + 9 = 0
∴ x3 + 33 = (x + 3) (x2 – 3x + 9) = 0
⇒ x3 = – 27Correct Option: D
x + 3 = 1 3 x ⇒ x2 + 9 = 1 3x
⇒ x2 + 9 = 3x
⇒ x2 – 3x + 9 = 0
∴ x3 + 33 = (x + 3) (x2 – 3x + 9) = 0
⇒ x3 = – 27
- 9x2 + 25 – 30x can be expressed as the square of
-
View Hint View Answer Discuss in Forum
9x2 + 25 – 30x
= (3x)2 + (5)2 – 2 × 3x × 5
= (3x – 5)2Correct Option: C
9x2 + 25 – 30x
= (3x)2 + (5)2 – 2 × 3x × 5
= (3x – 5)2
-
For real a, b, c if a2 + b2 + c2 = ab + bc + ca, the value of a + c is b
-
View Hint View Answer Discuss in Forum
a2 + b2 + c2 = ab + bc + ca
⇒ 2a2 + 2b2 + 2c2 – 2ab – 2bc – 2ca = 0
⇒ a2 + b2 – 2ab + b2 + c2 – 2bc + c2 + a2 – 2ca = 0
⇒ (a – b)2 + (b – c)2 + (c – a)2 = 0
∴ a – b = 0 ⇒ a = b
b – c = 0 ⇒ b = c
c – a = 0 ⇒ c = a
∴ a = b = c∴ a + c = 2a = 2 b a Correct Option: C
a2 + b2 + c2 = ab + bc + ca
⇒ 2a2 + 2b2 + 2c2 – 2ab – 2bc – 2ca = 0
⇒ a2 + b2 – 2ab + b2 + c2 – 2bc + c2 + a2 – 2ca = 0
⇒ (a – b)2 + (b – c)2 + (c – a)2 = 0
∴ a – b = 0 ⇒ a = b
b – c = 0 ⇒ b = c
c – a = 0 ⇒ c = a
∴ a = b = c∴ a + c = 2a = 2 b a
-
If a + 1 = b + 1 = c + 1 , where a ≠ b ≠ c ≠ 0, then the value of a2b2c2 b c a
-
View Hint View Answer Discuss in Forum
a + 1 = b + 1 = c + 1 b c a ⇒ abc + c = abc + a = abc + b bc ac ab ⇒ c = a = b bc ac ab ⇒ 1 = 1 = 1 b c a
⇒ a = b = c = 1
∴ a2b2c2 = 1Correct Option: D
a + 1 = b + 1 = c + 1 b c a ⇒ abc + c = abc + a = abc + b bc ac ab ⇒ c = a = b bc ac ab ⇒ 1 = 1 = 1 b c a
⇒ a = b = c = 1
∴ a2b2c2 = 1
-
Let x = √13 + √11 and y = 1 then the value of 3x2 – 5xy + 3y2 is √13 − √11 x
-
View Hint View Answer Discuss in Forum
x = √13 + √11 √13 − √11
On rationalising the denominator,= √13 + √11 × √13 + √11 √13 − √11 √13 + √11 = (√13 + √11)2 (√13)2 − (√11)2 = 13 + 11 + 2√143 13 − 11 = 24 + 2√143 = 12 + √143 2 ∴ y = 1 = 1 x 12 + √143 = 1 × 12 − √143 12 + √143 12 − √143 = 12 − √143 = 12 − √143 144 − 143
∴ x – y = 12 + √143 – 12 + √143 = 2√143
and
xy = (12 + √143)(12 – √143)
= 144 – 143 = 1
∴ 3x2 – 5xy + 3y2 = 3x2 – 6xy + 3y2 + xy
= 3 (x – y)2 + xy
= 3 (2√143)2 + 1
= 3 × 4 × 143 + 1 = 1716 + 1
= 1717Correct Option: A
x = √13 + √11 √13 − √11
On rationalising the denominator,= √13 + √11 × √13 + √11 √13 − √11 √13 + √11 = (√13 + √11)2 (√13)2 − (√11)2 = 13 + 11 + 2√143 13 − 11 = 24 + 2√143 = 12 + √143 2 ∴ y = 1 = 1 x 12 + √143 = 1 × 12 − √143 12 + √143 12 − √143 = 12 − √143 = 12 − √143 144 − 143
∴ x – y = 12 + √143 – 12 + √143 = 2√143
and
xy = (12 + √143)(12 – √143)
= 144 – 143 = 1
∴ 3x2 – 5xy + 3y2 = 3x2 – 6xy + 3y2 + xy
= 3 (x – y)2 + xy
= 3 (2√143)2 + 1
= 3 × 4 × 143 + 1 = 1716 + 1
= 1717